2021
DOI: 10.1017/psrm.2021.28
|View full text |Cite
|
Sign up to set email alerts
|

The diplomatic burden of pandemics: lessons from malaria

Abstract: This note seeks to understand the extent of the disruptions to international relations caused by pandemics, focusing on one globally-endemic disease: malaria. We posit that longstanding diseases such as malaria have the potential to undermine the political ties of nation states, as well as the many benefits of these connections. Our argument is tested empirically using both directed-dyadic and monadic data, while incorporating methods that account for endogeneity and other relevant concerns. We find that the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…For example, a study by Gallup & Sachs (2001) showed that during the latter part of the 20th century, malarial countries grew 1.3% less per person per year compared with non-malarial states, even after accounting for initial poverty, economic policy, tropical location, and life expectancy. Similarly, Bagozzi & Koren (2021) find that an increase from minimum to maximum in a given state's malarial prevalence decreases the probability that affected states will receive a diplomatic mission from another state by 6-7%. Diseases such as HIV/AIDS, malaria, tuberculosis, influenza, cholera, and SARS have all reached pandemic levels in the last century with devastating effects (Bagozzi & Koren, 2021).…”
Section: Theoretical Motivationmentioning
confidence: 89%
See 2 more Smart Citations
“…For example, a study by Gallup & Sachs (2001) showed that during the latter part of the 20th century, malarial countries grew 1.3% less per person per year compared with non-malarial states, even after accounting for initial poverty, economic policy, tropical location, and life expectancy. Similarly, Bagozzi & Koren (2021) find that an increase from minimum to maximum in a given state's malarial prevalence decreases the probability that affected states will receive a diplomatic mission from another state by 6-7%. Diseases such as HIV/AIDS, malaria, tuberculosis, influenza, cholera, and SARS have all reached pandemic levels in the last century with devastating effects (Bagozzi & Koren, 2021).…”
Section: Theoretical Motivationmentioning
confidence: 89%
“…Similarly, Bagozzi & Koren (2021) find that an increase from minimum to maximum in a given state's malarial prevalence decreases the probability that affected states will receive a diplomatic mission from another state by 6-7%. Diseases such as HIV/AIDS, malaria, tuberculosis, influenza, cholera, and SARS have all reached pandemic levels in the last century with devastating effects (Bagozzi & Koren, 2021). Developing, and especially conflict-torn countries with already weak infrastructures, poor safety nets, and shaky health systems, bear a much greater cost of pandemics and often suffer from graver long-term consequences of diseases and pandemics (Ataguba, 2020).…”
Section: Theoretical Motivationmentioning
confidence: 89%
See 1 more Smart Citation
“…However, Koreans faced the brunt of the malaria epidemic, which was worsened in many regions by agricultural and industrial expansion, and, eventually, by the military government established in 1938 [ 23 ]. This highlights the need for a holistic approach to the SDGs, recognising that addressing health challenges like malaria requires the involvement of multiple sectors beyond healthcare [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%